Integrated analysis of muscle transcriptome, miRNA, and proteome of Chinese indigenous breed Ningxiang pig in three developmental stages - Chen, Wenwu; Xiao, Yu; Yang, Fang; Liufu, Sui; Gong, Yan; Li, Zhi; Zhang, Shuo; Tang, Shengguo; Li, Biao; Ma, Haiming (Frontiers in Genetics, 2024)
The Ningxiang pig, a distinguished local breed in China, is recognized for its good meat quality traits. This study examines the proteomics of Ningxiang pigs at three developmental stages and delves into the upstream transcriptomics of these proteomics. Such an analysis facilitates a deeper understanding of the molecular interplay between proteins and transcriptomes in the Ningxiang pig muscle, influencing muscle growth and development. In this research, we analyzed the muscles of Ningxiang pigs at three developmental stages: 30 days in weaned piglets, 90 days in nursery pigs, and 210 days in late fattening pigs. There a total of 16 differentially co-expressed miRNAs (ssc-miRNA-1, ssc-miRNA-378, ssc-miRNA-143, ssc-miRNA-30e etc.), 74 differentially co-expressed mRNA (PLIN3, CPT2, IGF2 and HSP90AB1 etc.) have been identified in the three stages. 572 differentially abundant proteins (DAPs) (APOC3, NDUFA2, HSPD1, ATP5E, PDHA1 etc.) were readily identified by comparing different time periods. According to the KEGG enrich pathway results that DAPs most enriched in growth and development pathways, immune mechanism pathways and maintaining functions of physical. Through short time-series expression miner (STEM) association analysis, a total of 571 negative miRNA-mRNA interaction pairs and 2 negative miRNA-mRNA-protein (Chr05_11955-Pig.17268.1-ATP5F1B, ssc-miR-194a-3p-Pig.15802.1-ACY1) interaction pairs were found. Our study provides a theoretical basis on molecular 2 mechanism for the study of IMF deposition, muscle growth and immunity in Ningxiang pig breed.